2006
DOI: 10.4103/0019-5545.31559
|View full text |Cite
|
Sign up to set email alerts
|

The course of bipolar disorder in rural India

Abstract: Aim:To examine the naturalistic course of bipolar disorder in a rural, community-based, partially treated cohort.Methods:All patients diagnosed with bipolar disorder during an epidemiological survey (n=34) in a rural area in India were followed longitudinally using standardized instruments, and the life-chart method used to examine their course.Results:Seven (26%) of the 27 patients evaluated directly had not received any treatment whatsoever. Four patients (15%) had experienced rapid-cycling at some time; pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…The Asian studies have noted lower prevalence rates of SUD when compared to the Western literature (Chopra et al, 2006;Karthick et al, 2015a;Munoli et al, 2014). Male gender (Ahmadi et al, 2001;Hapangama et al, 2013) and low socio-economic status (Sedain, 2013) were independently associated with increased rates of substance use.…”
Section: Influence Of Substance Use Disorder (Sud)mentioning
confidence: 96%
See 4 more Smart Citations
“…The Asian studies have noted lower prevalence rates of SUD when compared to the Western literature (Chopra et al, 2006;Karthick et al, 2015a;Munoli et al, 2014). Male gender (Ahmadi et al, 2001;Hapangama et al, 2013) and low socio-economic status (Sedain, 2013) were independently associated with increased rates of substance use.…”
Section: Influence Of Substance Use Disorder (Sud)mentioning
confidence: 96%
“…Few studies have conducted prospective follow-up to ascertain the illness course (Chopra et al, 2006;Khess et al, 1997). On studying the typology of mood recurrences, manic episodes predominated the illness course of bipolar illness observed in the Asian (Avashthi et al, 1996;Chopra et al, 2006;Karthick et al, 2015a;Khanna et al, 1992;Ramdurg and Kumar, 2013;Rangappa et al, n.d.;Yazıcı and Cakır, 2012) and the Middle East regions (Osher et al, 2000). One study found that the patients spent more percent time in the manic phases when the total duration of illness is considered (Karthick et al, 2015a).…”
Section: The Course Of Bipolar Disordermentioning
confidence: 99%
See 3 more Smart Citations